Polygamy in Primetime : Media, Gender, and Politics in Mormon Fundamentalism - Bennion, Janet, 1964- (Brandeis series on gender, culture, religion & law., 2012)
A provocative look at the costs and benefits of polygamy among western fundamentalist Mormon women.